Elementary School English Teachers’ Self-assessment on their Teaching Competence: Challenges and Development Needs - Harwanto, Novie Feronika; Herawarman, Narendra Setia (UM Purwokerto Press, 2025)
Teacher competence is vital for improving the quality of education. However, many English teachers encounter challenges in developing their teaching competence. This study examined how elementary school English teachers evaluate their teaching competence. The main goal was to find out about the pedagogical, professional, social, and personal competencies that would require further development, as well as professional development strategies. The study participants were teachers from Christian primary schools in Semarang and Salatiga. Data were collected using self-assessment questionnaires and interviews. The findings revealed that social competence was given the highest assessment, while the lowest assessment was given to pedagogical competence. Therefore, this study suggested organizing further training programs to equip teachers with better pedagogical and professional competence in order to cope with the current demand of 21st-century education.